Vergleich von Chest Pain Units und Stroke Units: Elementare Bausteine der vaskulären Akutversorgung: Vergleich von Struktur, Zertifizierung, Qualitätserfassung und Vergütung - Breuckmann, Frank (Herz, 2020)
BACKGROUND: Chest pain units (CPU) and stroke units (SU) have both become established as essential components of clinical emergency care. For both instances dedicated certification processes are installed. Up to summer 2020, 290 CPUs and 335 SUs have been successfully certified. OBJECTIVE: The aim of this review is to compare the structures and the current certification situation of CPUs and SUs. Also, the younger CPU certification process is compared to the long established SU certification standard. MATERIAL UND METHODS: The comparison includes the historical background, the certification process, quality benchmarking, possible additive structures, the current status of certification in Germany, the transfer of the concept to the European level as well as reimbursement issues. RESULTS: Both certification concepts show clear analogies. Evidence for SUs is supported by a positive Cochrane analysis and for CPUs there are many studies from the German CPU registry. The main differences include a uniform CPU system versus a multistep SU system of certification. Furthermore, SU have obligatory elements of quality documentation but only facultative quality indicator assessment for CPUs. From an economic viewpoint operation and procedural key (OPS) numbers guarantee a better reflection of the use of resources in the complex treatment of stroke, which could not yet be established for CPUs. CONCLUSION: The well-established CPU concept could additionally benefit from a superordinate quality control. Adequate quality benchmarking appears to be fundamental for gap analyses and for the establishment of a separate remuneration structure. In this respect the German Society for Cardiology as the certifying institution is required to establish an appropriate mechanism within the framework of regular updates of criteria.